Penerapan Metode Analytical Hierarchy Process ( AHP )pada Sistem Pendukung Keputusan Pemilihan MahasiswaBerprestasi Menggunakan Framework Laravel(Studi Kasus : Institut Sains & Teknologi AkprindYogyakarta) - Erna Kumalasari Nurnawati (Jurnal Masyarakat Informatika, 2016)
Outstanding Student Selection is one of the activities which is held once every year inAKPRIND Institute of Science & Technology Yogyakarta. The first winner will be sent tothe Kopertis level. Outstanding Student Selection process that has lasted still not usecomputerized system. One of the systems that can be applied is the decision supportsystem with a method and a tool. The method that implemented in this system isAnalytical Hierarchy Process (AHP) method. This method chosen because it can break acomplex problem into sub-sub problems and arrange it to an hierarchy. The tool thatused in this system is Laravel framework. This Decision Support System in OutstandingStudent Selection can help Administration of Student and Alumnus Bureau with the resultof the calculation that applying AHP method and the result of the calculation thatapplying Mawapres Sarjana 2015 guide. Decision Support System in Outstanding StudentSelection is a system that could support the decision making process. This system isexpected to make the decision making process more easy and faster.